Biological Invasions And Biodiversity Threats Linked To Genetically Modified Organisms - Yuvaraj S; Sumitha.E; Sunitha C Mesta (Revista Electronica de Veterinaria, 2024)
Concerns about biological invasions and their potential impact on biodiversity have come to light due to GMOs. The introduction of GMOs into natural ecosystems carries with it several possible risks that may result in negative effects which are, however, unintentional. That is, the GMOs having traits designed for increased productivity on the farm could also give them an added advantage in terms of invasiveness. These attributes could allow GMOs to outcompete native species by enhancing reproduction rates and providing resistance to pests and diseases, as well as improving resource utilization. The loss of indigenous flora and fauna leads to changes in welfare systems and can threaten biodiversity in a second step. The possibility of gene flow between GMOs and their wild relatives is a major concern because hybridization can lead to the creation of new species with unknown consequences for the environment. Concerns with respect to the transfer of transgenes from genetically modified organisms (GMOs) to wild populations relate to the stability and integrity of natural ecosystems. In addition, hybridization may take place between the introduced genes and other members of the population, leading to the production of hybrids that have a competitive advantage over their non-GMO counterparts. The implementation through regulatory measures is important in reducing these risks. Environmental risk assessments need to be ascertained for detecting potential effects that could be exerted by genetically modified organisms (GMOs) toward ecosystems and biodiversity prior to allowing their release. Implementing containment strategies such as geographical limits or physical barriers plays a role in stopping unintentional spread and interactions with the environment. To detect and control any unforeseen environmental variations, regular monitoring and surveillance systems are very important. Even after these steps, there are still knowledge data gaps that need for more research on long-term impacts GMOs have on biodiversity. It is important to understand how GMOs interact with other stressors as well such as habitat loss and climate change to be able to formulate complete management methods. An intricate and flexible approach is necessary as we navigate the challenging landscape of agricultural innovation to reap the benefits that genetically modified organisms (GMOs) can bring while maintaining the delicate balance of natural ecosystems and biodiversity.